2′β‐Fluoro‐Tricyclo Nucleic Acids (2′F‐tc‐ANA): Thermal Duplex Stability, Structural Studies, and RNase H Activation. Issue 43 (13th June 2017) - Istrate, Alena; Katolik, Adam; Istrate, Andrei; Leumann, Christian J.
Abstract: We describe the synthesis, thermal stability, structural and RNase H activation properties of 2′β‐fluoro‐tricyclo nucleic acids (2′F‐tc‐ANA). Three 2′F‐tc‐ANA nucleosides (T, 5Me C and A) were synthesized starting from a previously described fluorinated tricyclo sugar intermediate. NMR analysis and quantum mechanical calculations indicate that 2′F‐tc‐ANA nucleosides prefer sugar conformations in the East and South regions of the pseudorotational cycle. UV‐melting experiments revealed that non‐consecutive insertions of 2′F‐tc‐ANA units in DNA reduce the affinity to DNA and RNA complements. However, an oligonucleotide with five contiguous 2′F‐tc‐ANA‐T insertions exhibits increased affinity to complementary RNA. Moreover, a fully modified 10‐mer 2′F‐tc‐ANA oligonucleotide paired to both DNA (+1.6 °C/mod) and RNA (+2.5 °C/mod) with significantly higher affinity compared to corresponding unmodified DNA, and similar affinity compared to corresponding tc‐DNA. In addition, CD spectroscopy and molecular dynamics simulations indicate that the conformation of the 2′F‐tc‐ANA/RNA duplex is similar to that of a DNA/RNA duplex. Moreover, in some sequence contexts, 2′F‐tc‐ANA promotes RNase H‐mediated cleavage of a complementary RNA strand. Taken together, 2′F‐tc‐ANA represents a nucleic acid analogue that offers the advantage of high RNA affinity while maintaining the ability to activate RNase H, and can be considered a prospective candidate for gene silencing applications. Abstract : Gene in a bottle : The synthesis and biophysical properties of 2′β‐fluoro‐tricyclo nucleic acids (2′F‐tc‐ANA) are described. Overall, 2′F‐tc‐ANA represents a nucleic acid analogue with high RNA affinity while maintaining the ability to activate RNase H, and can be considered a prospective candidate for gene silencing applications.